Cytotoxicity of eurycoma longifolia, nigella sativa and hibiscus sabdariffa on cervical and ovarian cancer cell lines - 'Afif Raihan binti Abdullah
Cervical and ovarian cancers are the lethal gynaecological malignancies that affect the local health scene among women. Eurycoma longifolia, Nigella sativa and Hibiscus sabdariffa are widely used as herbal remedies and natural supplements in Malaysia. The current study is designed to investigate the cytotoxic effects of standardised quassinoid E. longifolia (TAF 273), N. sativa (NSE) and H. sabdariffa (HSE) extracts on cervical cancer (HeLa) and ovarian cancer (Caov-3) cells and the mechanism of cell death. The cytotoxicity of TAF 273, NSE, and HSE were evaluated using MTT assay and the mode of cell death was detected by Hoechst 33258 nuclear staining. The analysis of apoptosis and cell cycle arrest were assessed via flow cytometry. The gene expression of Bax, Bcl-2 and caspase-3 were investigated through real-time PCR. The findings showed that TAF 273 suppressed the cell growth of Caov-3 with the lowest IC50 value (5.3µg/mL), comparable to the cisplatin (IC50 value of 6.07 ± 1.87 µM; ~6.1 µM). The IC50 values of TAF 273 on HeLa as well as NSE and HSE on both Caov-3 and HeLa were however not identified. TAF 273 and cisplatin showed no toxicity on normal human ovarian surface epithelial cells (nHOSEpiC). The characteristics of apoptosis such as cell shrinkage, chromatin condensation and nuclei fragmentation were found following TAF 273 and cisplatin treatment. The flow cytometry analyses showed that TAF 273 and cisplatin induced the apoptosis on Caov-3 in dose- and time-dependent manner and arrested the cell cycle at G2 phase. The real-time PCR results showed that TAF 273 down-regulated the Bax, Bcl-2, and caspase-3 expression. Meanwhile, cisplatin up-regulated the Bax and caspase-3 and down-regulated the Bcl-2 expression. Results from this study suggests that TAF 273 was cytotoxic on Caov-3 cells through the induction of the apoptosis via the mitochondrial pathway, initiated by proteins other than Bax and it was executed through other group of executioner caspase or via caspase- independent pathway. The output of this study may indicate the potential of the standardised quassinoid of Eurycoma longifolia extract in the successful treatment of ovarian cancer as part of cancer therapy.